Occupational safety and health improvement in mechanical fasteners manufacturing company - Iskandar Zukarnain Md. Noor, 1986-; Abd. Rahman Abdul Rahim; Fakulti Kejuruteraan Mekanikal (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2010